Features of changes in mechanical and tribological characteristics of multilayer coatings (TiZrNbYAl)N - Mukhamedova А.И.; Pogrebnyak А.Д.; Uazyrkhanova Г.К.; Rakhadilov Б.Қ. (Recent Contributions to Physics, 2024)
In this work, the adhesive and tribological characteristics of (TiZrNbYAl)N multilayer coatings were studied. The main goal of this work is to assess the influence of the number of layers on the adhesive and tribological characteristics of the (TiZrNbYAl)N coating deposited on 12Х18Н9Т steel substrates. A study of the distribution of elements over the depth of coatings using Auger electron spectroscopy showed that chemical elements are distributed quite evenly over the cross section of the coatings and the element distribution curves have sharp peaks. The presence of iron in the coating composition at a depth of more than 2 microns on the coating side indicates that an increase in electrical displacement ensures reliable adhesion of the coating to the steel substrate, which is confirmed by the results of testing the coatings for adhesive strength. An increase in the application time of each individual layer at Upp=-100 V and P= 4×10-3 Torr leads to an uneven distribution of elements throughout the thickness of the coatings and the formation of a relatively wide transition coating-substrate layer. Tests of the adhesive strength of coatings have shown that all coatings wear out when scratched, but do not peel off, i.e., they are destroyed by a cohesive mechanism associated with plastic deformation and the formation of fatigue cracks in the coating material. Different coating modes correspond to different values of acoustic emission depending on the load. It was determined that the coatings obtained at Upp =-100 V; P = 4×10-3 Torr showed high adhesive strength and some degree of delamination in the scratch area at the maximum test load. The results of tribological studies showed that (TiZrNbYAl)N coatings have a high friction coefficient, the average value of which is μ=0.85-0.95. Such values can be explained by the high roughness of wear tracks due to cohesive destruction of coatings.